NOVOS OLHARES A RESPEITO DO PROCESSO DE ENSINO APRENDIZAGEM NA NATAÇÃO: REVISÃO SISTEMÁTICA - NUNES, Leonardo Geamonond; FRANCO, Raquel (RENEF, 2020)
The aim of the study was to carry out a systematic review of the swimming teaching process and, consequently, answer the following question: Does the pedagogy of swimming have relevant empirical content? Methods: Complete articles were analyzed and published between 2010 and 2019 in Portuguese and English, in the following databases: SCIELO and ERIC. Results: Prior to initiation into four culturally determined strokes, learning must master the fundamentals of swimming and other alternative strokes. The learnings presented the control of the own body in aquatic environment and the domain in manipulation of objects during the propulsion, so that they can execute technical techniques. Conclusion: This systematic review aims to address principles and fundamentals for whom the teacher is dedicated to start in water sports and can deconstruct his teaching program aimed only at four different cultural levels. We must present other pedagogical paths that must be tracked or recognize and interpret the demands of the learned task, in this way the new reports showing the control of the own body and the environment that uses inserts in a satisfactory way.